2015
DOI: 10.1007/978-3-319-25013-7_7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Impediments Blocking Internet of Things Adoption by Governments

Abstract: Abstract. The Internet of Things (IoT) has high promises and might provide many benefits, yet has been given scant attention in e-government literature. Within the IoT, physical objects, "things", are networked and connected to the Internet. These "things" are able to identify themselves to and communicate with other devices or "things". There are many impediments blocking the adoption of IoT, and there is limited insight in these barriers. In this paper, impediments for the adoption of IoT are investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…75]. When people or things act (or react) on an environment, that environment can be changed in unexpected ways [33]. Generally, actors follow a schema or "shared rules" such as norms, values, beliefs, and assumptions [34].…”
Section: Cas Elements Of Data Infrastructuresmentioning
confidence: 99%
“…75]. When people or things act (or react) on an environment, that environment can be changed in unexpected ways [33]. Generally, actors follow a schema or "shared rules" such as norms, values, beliefs, and assumptions [34].…”
Section: Cas Elements Of Data Infrastructuresmentioning
confidence: 99%
“…Data privacy is a significant issue in IoT as well, especially in urban setting. In case studies [30], data privacy and security were found to be the main impediments on the strategic level for the introduction of IoT for e-government. Data accuracy is another issue critical for the implementation of IoT in smart cities.…”
Section: Data Security and Data Privacymentioning
confidence: 98%
“…Data privacy is a significant issue in IoT as well, especially in urban setting. In case studies (Brous & Janssen, 2015), data privacy and security were found to be the main impediments on the strategic level for the introduction of IoT for digital government. Data accuracy is another issue, which is critical for the implementation of IoT in smart cities.…”
Section: Data Security and Data Privacymentioning
confidence: 98%